An update on targeted therapies in systemic sclerosis based on a systematic review from the last 3 years - Corrado Campochiaro (Arthritis Research & Therapy, 2021)
Abstract New molecular mechanisms that can be targeted with specific drugs have recently emerged for the treatment of systemic sclerosis (SSc) patients. Over the past 3 years, the achievement of one large phase 3 trial has led to the approval by drug agencies of the first drug licenced for SSc-related interstitial lung disease. Given this exciting time in the SSc field, we aimed to perform a systemic literature review of phase 1, phase 2 and phase 3 clinical trials and large observational studies about targeted therapies in SSc. We searched MEDLINE/PubMed, EMBASE, and ClinicalTrials.gov for clinical studies from 2016 with targeted therapies as the primary treatment in patients with SSc for skin or lung involvement as the primary clinical outcome measure. Details on the study characteristics, the trial drug used, the molecular target engaged by the trial drug, the inclusion criteria of the study, the treatment dose, the possibility of concomitant immunosuppression, the endpoints of the study, the duration of the study and the results obtained were reviewed. Of the 973 references identified, 21 (4 conference abstracts and 17 articles) were included in the systematic review. A total of 15 phase 1/phase 2 clinical trials, 2 phase 3 clinical trials and 2 observation studies were analysed. The drugs studied in phase 1/phase 2 studies included the following: inebilizumab, dabigatran, C-82, pomalidomide, rilonacept, romilkimab, tocilizumab, tofacitinib, pirfenidone, lenabasum, abatacept, belimumab, riociguat, SAR100842 and lanifibranor. All but 3 studies were performed in early diffuse SSc patients with different inclusion criteria, while 3 studies were performed in SSc patients with interstitial lung disease (ILD). Phase 3 clinical trials investigated nintedanib and tocilizumab. Nintedanib was investigated in SSc-ILD patients whereas tocilizumab focused on early diffuse SSc patients with inflammatory features. Two observational studies including > 50 patients with rituximab as the targeted drug were also evaluated. All these studies offer a real hope for SSc patients. The future challenges will be to customize patient-specific therapeutics with the goal to develop precision medicine for SSc.